Does Perceived Usefulness, Perceived Ease of Use, And Perceived Risk Has Influence on Intention To Use E-Wallet? - Tan Christabel Michaela Devina; Hendro Lukman (VISA: Journal of Vision and Ideas, 2024)
Aligned with technological advancements, digital-based financial services have undergone development, leading to continuous changes and innovations in online payment methods. Among these innovations is the emergence of electronic wallets, known as electronic wallet, (e-wallets) as a non-cash payment tool. Despite the benefits and conveniences offered, e-wallets are vulnerable to internet criminal activity that concerns users. However, e-wallets are noted as the most popular payment method in Indonesia, constituting 81% of transactions. This research aims to analyze the variables of perceived usefulness, perceived ease of use, and perceived risk in the intention to use e-wallets among e-wallet users. The research specifically chose e-wallet users aged at least 17 with a minimum monthly income of Rp 2 million as subjects. The research uses primary data, which is collected through the distribution of digital questionnaires using convenience sampling followed by snowball sampling methods, as well as simple random sampling. Data from 114 respondents is collected and analyzed using multiple linear regression. The research results show that perceived usefulness and perceived ease of use influence e-wallet users' intention to use e-wallets, while perceived risk does not influence e-wallet users' intention. The implication of this research is that e-wallet service providers are expected to provide e-wallets that offer significant added value to users' lives and are user-friendly, thereby fostering users' intention to use e-wallets.